Cardinal points : poems - Pettit, Michael (Iowa poetry prize., 1988)
Strung throughout the book are poems based on the Scottish photographer Eadwaerd Muybridge's Animal Locomotion, a historic photographic document. Pettit uses these pioneering images as the basis for his poetic dreaming, and the result is a poignant, integrated sequence of highly moving poems, studded between other vivid lyrics.